Leachate emissions of short- and long-chain per- and polyfluoralkyl substances (PFASs) from various Norwegian landfills - Knutsen, Heidi; Mæhlum, Trond; Haarstad, Ketil; Slinde, Gøril Aasen; Arp, Hans Peter H (Environmental science--processes & impacts, 2019)
Restrictions on the use of long-chain per- and polyfluoralkyl substances (PFASs) has led to substitutions with short-chain PFASs. This study investigated the presence of four short-chain PFASs and twenty-four long-chain PFASs in leachate and sediment from ten Norwegian landfills, including one site in Svalbard, to assess whether short-chain PFASs are more dominant in leachate. PFASs were detected in all sites. Short-chain PFASs were major contributors to the total PFAS leachate concentrations in six of ten landfills, though not in Svalbard. In sediment, long-chain PFASs such as perfluorooctanesulfonate (PFOS) and PFOS-precursors were dominant. Short-chain PFAS leachate concentrations ranged from 68 to 6800 ng L −1 (mean: 980 ± 1800; median: 360 ng L −1 ), whereas long-chain concentrations ranged from 140 to 2900 ng L −1 (mean: 530 ± 730; median: 290 ng L −1 ). Sediment concentrations, which contained mainly long-chain PFASs, ranged from 8.5 to 120 μg kg −1 (mean: 47 ± 36; median: 41 μg kg −1 ). National release from Norwegian landfills to the environment was estimated to be 17 ± 29 kg per year (median: 6.3 kg per year), which is in the same range as national emissions from the US, China and Germany after normalizing the data to a per capita emission factor (3.2 ± 5.5 mg per person per year). Results from this study are compared with previous and current studies in other countries, indicating a general trend that short-chain PFASs are dominating over long-chain PFASs in landfill leachate emissions. Restrictions on the use of long-chain per- and polyfluoralkyl substances (PFASs) has led to substitutions with short-chain PFASs.